Heat transfer and pressure drop in a heat exchanger with a helical pipe containing inside springs - Yildiz, C; Bicer, Y; Pehlivan, D (Pergamon-Elsevier Science Ltd, 1997)
In this study, a heat exchanger which is constructed by placing spring-shaped wires with varying pitch within a helical pipe was considered. The pressure drop and the overall heat transfer rates were measured for the case of air flow at various Reynolds numbers inside and constant water flow outside. The results show that the Nusselt number increases with decreasing pitch/wire diameter ratio, as much as five times with respect to an empty pipe for the same Dean number, and for;his relationship, a tentative empirical formula is suggested. Although a rise up to 10 times in the inlet/outlet pressure drop values with respect to the conventional empty helical case is observed, the increase in Nusselt number, naturally, reflects an increase of about 30% in the effectiveness of the helical heat exchanger. (C) 1997 Elsevier Science Ltd.
Keywords: heat exchanger; helical pipe; spring; efficiency